Breast cancer treatment across health care systems: Linking electronic medical records and state registry data to enable outcomes research. Issue 1 (24th September 2013) - Kurian, Allison W.; Mitani, Aya; Desai, Manisha; Yu, Peter P.; Seto, Tina; Weber, Susan C.; Olson, Cliff; Kenkare, Pragati; Gomez, Scarlett L.; de Bruin, Monique A.; Horst, Kathleen; Belkora, Jeffrey; et al.
Abstract : BACKGROUND: Understanding of cancer outcomes is limited by data fragmentation. In the current study, the authors analyzed the information yielded by integrating breast cancer data from 3 sources: electronic medical records (EMRs) from 2 health care systems and the state registry. METHODS: Diagnostic test and treatment data were extracted from the EMRs of all patients with breast cancer treated between 2000 and 2010 in 2 independent California institutions: a community‐based practice (Palo Alto Medical Foundation; "Community") and an academic medical center (Stanford University; "University"). The authors incorporated records from the population‐based California Cancer Registry and then linked EMR‐California Cancer Registry data sets of Community and University patients. RESULTS: The authors initially identified 8210 University patients and 5770 Community patients; linked data sets revealed a 16% patient overlap, yielding 12, 109 unique patients. The percentage of all Community patients, but not University patients, treated at both institutions increased with worsening cancer prognostic factors. Before linking the data sets, Community patients appeared to receive less intervention than University patients (mastectomy: 37.6% vs 43.2%; chemotherapy: 35% vs 41.7%; magnetic resonance imaging: 10% vs 29.3%; and genetic testing: 2.5% vs 9.2%). Linked Community and University data sets revealed that patients treated at both institutions received substantially more interventions (mastectomy: 55.8%; chemotherapy: 47.2%; magnetic resonance imaging: 38.9%; and genetic testing: 10.9% [ P  < .001 for each 3‐way institutional comparison]). CONCLUSIONS: Data linkage identified 16% of patients who were treated in 2 health care systems and who, despite comparable prognostic factors, received far more intensive treatment than others. By integrating complementary data from EMRs and population‐based registries, a more comprehensive understanding of breast cancer care and factors that drive treatment use was obtained. Cancer 2014;120:103–111 . © 2013 American Cancer Society . Abstract : Surveillance, Epidemiology, and End Results data were integrated with electronic medical records from 2 health care systems to analyze outcomes in patients with breast cancer. A substantial number of patients sought breast cancer treatment from 2 health care systems and, despite having a similar cancer prognosis, received far more intensive interventions than other patients did.